Racionalidade neoliberal e sensibilização para a inclusão escolar de deficientes - Machado, Fernanda de Camargo (2015)
"Sensitizing" is one of the most often used verbs in the current inclusion policies in Brazil. Several documents have highlighted the historical urgency of access, participation and acceptance of all, particularly in the regular school, and the interaction between disabled and non-disabled people has been strongly encouraged in Contemporaneity. This thesis aims at problematizing the provenience, emergence, functioning and effects of this call in this country. In order to do that, it has addressed a set of documents, including magazines, handbooks, tests, guides and campaigns intended to raise awareness of the inclusion of disabled people by the school community. The central focus of this research has been to understand how neoliberal rationality has conducted modes of subjectivation from practices of sensitization for the inclusion of disabled students in school in Brazil. Such problematization has employed analytical tools developed by Michel Foucault, such as governmentality, government by the truth and subjectivation. Inspired by the genealogical method, the study has attempted to understand how we have taken up the sensitization practices as guidelines of self-conduct in relation to the disabled in the inclusive school. The analysis has evidenced the production of a ―pedagogy of sensitization to inclusion‖ that aims at mobilizing everyone to believe in the benefits, gains and advantages provided by active interaction with the disabled in the inclusive school. In those conditions, it has been possible to highlight the functionality of the sensitization practices to include the disabled in the school as practices of government of the self and the others which have been produced in the historical displacement from the risk of interacting to the risk of not interacting. On favoring the interest in the transformation of the self through partnerships between the disabled and the non-disabled and through leveling its very inclusive performance, the pedagogy of sensitization has become indispensable for both the consolidation and the maintenance of the inclusion regime of truth. Objectivation and subjectivation techniques that characterize other forms of conduction of conducts such as confession, direction of conscience and examination have been reshaped by the principles of cooperation and competitiveness, and this allows us to visualize the immanence between sensitization practices for the inclusion of the disabled in school and the neoliberal rationality in Brazil.